Extraction of protease from Anacardium occidentale (Cashew) fruit using response surface methodology - Shuhaimen, Muhammad Shahrain; Omar, Muhammad Nor; Abdullah, Erna Normaya; Ahmad, Mohammad Norazmi (2017)
Protease is a versatile industrial enzymes that is applicable in various industries including the food sector. Eventhough most commercial proteases are from animal and microbial origin, they each carries certain limitations involving religious, ethical and dietary concerns. Therefore, the discovery of proteases from plant as an alternative source should be given attention. In this study cashew (Anacardium occidentale) fruit, known to have dermatitic and anthelmintic properties, was chosen as source of protease, and the effect of the extraction process on its protease activity is evaluated. The extracted crude enzyme was optimized by using response surface methodology (RSM) using a central composite rotatable design (CCRD) with variables studied were pH (x1), CaCl2 (x2), mixing time (x3) and mass (x4). The quadratic model obtained from the results is significant (R2 = 0.9739). Based on the RSM model, the optimal extraction conditions were obtained at pH 6.42, 8.94 mM CaCl2, 5.62 min mixing time and 18.55 g sample mass that yields protease 6.251 unit/mL of crude extract.